Environment Protection as a Presumption of Sustainable Development - Premović, Jelena; Premović, Tamara (Journal of Economic Development, Environment and People, 2013)
Rapid economic growth and irrational use of natural resources in the last decades of the XX century have influenced the changes in the environmental sphere and to specific environmental problems. These processes in the global economy and society, caused a disturbance of the environment by increasing pollution of the environment. Emerging problems of the entire human society can be solved by applying the concept of sustainable growth and development and raising awareness about the necessity of implementation of basic environmental standards in business. In order to reduce the harmful effects of production processes on the environment and to help meet the objective of sustainable development outlined at the UN Conference on Environment and Development in Rio De Janeiro in 1992 the ISO 14000 Standards were created. The essence of sustainable development is responsible development that meets the current needs a way to rationally use natural resources to ensure meeting the needs of future generations and environment protection.